TRANSLATION ANALYSIS OF PHATIC EXPRESSIONS IN THE SERIES ENTITLED CEK TOKO SEBELAH: BABAK BARU - Kartika Sofiyanti; Mangatur Nababan (Translation and Linguistics (Transling), 2023)
This article analyzed Indonesian phatic expressions in the series entitled Cek Toko Sebelah: Babak Baru from episode 1-4. The objectives are to identify and classify the phatic expressions, identify translation techniques used, examine the forms shift, and assess the translation's accuracy and acceptability. This research is qualitative descriptive research, a single-embedded case study, and product-oriented research. Results show three forms of phatic expressions in the series; particle, word, and phrase. Furthermore, the analysis shows that four translation techniques are used: deletion, established equivalent, modulation, and paraphrase. Then, the translation quality in terms of accuracy and acceptability assessment result explains that the translation of Indonesian phatic expressions in Cek Toko Sebelah: Babak Baru is less accurate, resulting in an average score of 1.7.